Exploring the Financial Benefits of Mental Health in African Nations: Overcoming Mental Obstacles - Nsubuga, Moses (Happiness: Journal of Psychology and Islamic Science, 2023)
Governments in wealthier countries have taken an increasing interest in mental health in recent years, conscious of its impact on quality of life and the economic consequences of poor mental health. In Africa, however, mental health is still not given the attention and resources it needs, with the majority of the focus being on communicable disorders. This review of the literature looks at the economic effects of mental health in African countries, exploring the difficulties they face and how economic data can be used to push for more investment in mental health. It examines the available information, identifies any gaps in the evidence, and examines how mental health services are provided.  In high-income countries, NGOs have been demonstrated to be a significant factor in the financing, organization, and supply of mental health services, which is of great importance. In African countries, where mental health policy and infrastructure are more limited, NGOs have an even more essential part to play in removing obstacles to the establishment of mental health policy and practice.